Rescuing Ellisville Marsh : The Long Fight to Restore Lost Connections - Cody, Eric P., 1950- (Book collections on Project MUSE., 2023)
"For hundreds of years, farmers and fishing communities maintained the inlet to Ellisville Marsh, a picturesque piece of coastline ten miles south of Plymouth, Massachusetts. Recognized as one of the most environmentally sensitive and ecologically valuable places in the state, the salt marsh and estuary are home to a diverse array of wildlife and a range of habitats, including lowtide mudflats, a saltwater pond, intertidal zone, and fields of tall marsh grass. After agricultural and fishing activities faded away in the late twentieth century, it soon became apparent that protecting the marsh and its surroundings from development would not be enough to restore the natural equilibrium that had been lost when the inlet became blocked. Having witnessed government inaction over the years, Eric P. Cody and four other locals founded the Friends of Ellisville Marsh in 2007 to address erosion, revive tidal flows, and revitalize fisheries and wildlife in the face of climate change. Rescuing Ellisville Marsh presents the powerful case study of backyard activism, telling the story of a community that bonded with a natural place and decided to fight for it"--